Implementasi Kinerja Mesin Pemotong Kemplang Khas Palembang Berbasis Teknologi Internet Of Things (IOT) - slamet WIDODO; A.Bahri Joni M; Ahyar Supani (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Palembang is one of the areas in Indonesia that is known to have culinary tastes that are distinctive and delicious. The capital city of South Sumatra Province has a very diverse culinary wealth. Kemplang Palembang Fish Crackers is one of the traditional Palembang food with fish and tapioca flour as its ingredients. At this time many fish kemplang makers still use traditional methods using brass pirikan, with a large variety of holes at the bottom. This phenomenon is also carried out by DPTM program partners, namely Partners (1) Kemplang cracker business